Efficiency of integration crashing program and building information modeling on high rise building projects - Widyaningsih, Nunung; Purwoko Kusumo Bintoro, Bambang; Nasrul Huri Saputra, Ikra (International Journal of Engineering and Technology, 2019)
This study is to analyze the Efficiency of Integration of Crashing Program and Building Information Modeling in the High Rise Building Project. The method of sampling is done by using the Purposive Sampling method there are 60 people in total. From the sampling technique used in the research then the sample criteria used as primary data sources in this study are Project Manager, Site Manager, Engineering Head, Site Engineer, and Drafter. This study uses SEM analysis to assess the Integration Efficiency of Crashing Program and Building Information Modeling on Project performance (Time and Cost). The results of the Analysis of Integration of Crashing Program and BIM in the High Rise Building Project, Crashing Program and Building Information Modeling have an effect on Time and Cost Performance. Crashing Program (CP) provides efficiency on time performance and cost performance by 52%. Building Information Modeling (BIM) provides efficiency for time performance and cost performance by 50%. Integration of Crashing Program (CP) and Building Information Modeling (BIM) provides efficiency for the implementation of the High Rise Building project by 25%.Â